Filmgespräch: Afrikaleidoskop meets ARTE: Südafrikas Weg aus der Apartheid (Afrikaleidoskop meets ARTE, 2025)
As part of its film series "AfriKaleidoskop meets ARTE" the Africa Multiple Cluster of Excellence showed the ARTE documentary Südafrikas Weg aus der Apartheid – Teil 1: Suche nach Antworten, on May 8, 2025 What does justice mean in post-apartheid South Africa—and who gets to define it? Watch the powerful discussion recorded after the screening of the ARTE documentary ,Kulturhaus Neuneinhalb. Filmmaker Thomas Blom and scholar Patricia Pinky Ndlovu-Gatsheni reflect on memory, reconciliation, and the unfinished struggle for equality.